Transmission ratio distortion in the hybrid offspring of three mouse subspecies - Wagner, Jennifer Margaret (My University, 2010)
A crucial component of understanding the origin or new species is understanding how reproductive isolation evolves between divergent populations. The relative importance of Dobzhansky-Muller incompatibilities as compared to meiotic drivers in the origin of post-zygotic isolation therefore represents an important question in evolutionary biology. This study begins answering that question by identifying regions of significant transmission ratio distortion (TRD) in the F2 progeny of reciprocal intercrosses conducted between three wild-derived inbred mouse (Mus musculus) strains: WSB/EiJ, PWD/PhJ, and CAST/EiJ. Analysis of genotype data at 212 autosomal single nucleotide polymorphisms (SNPs) from across the genome revealed eleven significantly distorted regions in a WSB/EiJ X PWD/PhJ reciprocal intercross, of which seven were sex-specific, and eight significantly distorted regions in a WSB/EiJ X CAST/EiJ reciprocal intercross, of which all were sex-specific. Increased levels of TRD observed in the WSB/EiJ X PWD/PhJ reciprocal intercross as compared to the WSB/EiJ X CAST/EiJ reciprocal intercross suggest greater functional divergence of M. m. musculus than M. m. casteneus from M. m. domesticus. Additionally, the observation that the majority of TRD is sex-specific indicates that the sex chromosomes are important in establishing post-zygotic reproductive isolation. Based on the TRD found, as well as the sex ratios observed in each cross, it seems likely that Dobzhansky-Muller incompatibilities play a more important role than meiotic drivers in the origin of post-zygotic isolation in house mice.
54 p.
Keywords: Microbiology; Genetics